Evaluating clinical observation versus Spatial Frequency Domain Imaging (SFDI), Laser Speckle Imaging (LSI) and thermal imaging for the assessment of burn depth. Issue 2 (March 2019) - Ponticorvo, Adrien; Rowland, Rebecca; Baldado, Melissa; Burmeister, David M.; Christy, Robert J.; Bernal, Nicole P.; Durkin, Anthony J.
Highlights: Clinical examination is the standard for diagnosing burn severity. Accurate assessments at early time points are difficult but could provide benefit. We compared three imaging technologies to clinical assessment in a pig model. Only one technique outperformed clinical assessment. Spatial Frequency Domain Imaging could be a useful tool to aid clinical diagnosis. Abstract: While clinical examination is needed for burn severity diagnosis, several emerging technologies aim to quantify this process for added objectivity. Accurate assessments become easier after burn progression, but earlier assessments of partial thickness burn depth could lead to earlier excision and grafting and subsequent improved healing times, reduced rates of scarring/infection, and shorter hospital stays. Spatial Frequency Domain Imaging (SFDI), Laser Speckle Imaging (LSI) and thermal imaging are three non-invasive imaging modalities that have some diagnostic ability for noninvasive assessment of burn severity, but have not been compared in a controlled experiment. Here we tested the ability of these imaging techniques to assess the severity of histologically confirmed graded burns in a swine model. Controlled, graded burn wounds, 3 cm in diameter were created on the dorsum of Yorkshire pigs (n = 3, 45–55 kg) using a custom-made burn tool that ensures consistent pressure has been employed by various burn research groups. For each pig, a total of 16 burn wounds were created on the dorsal side. Biopsies were taken for histological analysis to verify the severity of the burn. Clinical analysis, SFDI, LSI and thermal imaging were performed at 24 and 72 h after burn to assess the accuracy of each imaging technique. In terms of diagnostic accuracy, using histology as a reference, SFDI (85%) and clinical analysis (83%) performed significantly better that LSI (75%) and thermography (73%) 24 h after the burn. There was no statistically significant improvement from 24 to 72 h across the different imaging modalities. These data indicate that these imaging modalities, and specifically SFDI, can be added to the burn clinicians' toolbox to aid in early assessment of burn severity.